Teacher's Efforts in Motivating Student Learning in Economics Subjects at SMAN 1 Laung Tuhup - Rinto Alexandro; Fendi Hariatama; Sri Rohaetin; Tonich Uda; Piramida Yunitha; Rahman . (JURNAL PENDIDIKAN, 2022)
Abstract The purpose of this research is to find out the efforts made by economics teachers in motivating students to study at SMA Muara Tupuh Filial SMAN 1 Laung Tuhup Murung Raya Regency. This research was conducted using qualitative approach. Qualitative research aims to obtain a complete picture of a thing according to the human view studied. By involving the principal, deputy principal, 1 teacher and 12 students of Muara Tupuh Filial SMAN 1 Laung Tuhup High School. The data can be through interviews with principals, vice principals, economics teachers and grade XI students.Based on the results of research and interviews showed that Economics teachers strive quite well in teaching and learning activities, so that students are quite motivated in participating in economic learning activities. The motivation of the students has gone well. This can be seen from the motivation that comes from the students, namely from the desire of students to learn, a happy attitude towards the eyes of economic students that shows that students have a desire and desire to succeed and students have hopes and ideals in the future that move them to always be active in learning so that their hopes and ideals can be realized. Keywords: teacher efforts, learning motivation, economic